(untitled) (Journal of Dhaka Medical College, 2010)
Objectives: To diagnose lumbar disc herniation by MRI, to compare the MRI findings with peroperative findings and to elucidate validity of MRI in pre-operative diagnosis of lumbar disc herniation. Methodology:The study was done between January 2008 to March 2009 with 40 patients (28 male and 12 female) who were clinically suspected as cases of lumbar disc herniation and was referred for MRI of Lumbo-sacral spine to the Radiology and Imaging department of Dhaka Medical College Hospital. Detail history, clinical examination and MRI of lumbo-sacral spine were performed in all cases and the Patients were followed up during the surgery. The peroperative findings were then correlated with MRI findings and for the validity of the study outcome, sensitivity, specificity, accuracy, positive predictive value and negative predictive values of MRI in the diagnosis of Lumbar disc herniation were calculated. Results: In this study 21(52.5%) cases were found in 3rd decade, 17(42.5%) cases in the 4th decade and 2 (5.0%) cases in 5th decade. Male female ratio of lumbar disc herniation is 2.33:1 (28:12). 60% of the study subjects were stressful and that of 40% was sedentary. Lumber disc herniation was mostly seen at L4-5 level (57.5%) and L5-S1 level (25%). MRI was 94.28% sensitive, 60% specific and showed an accuracy of 90%. Conclusion: This study established the use of MRI as the radiological investigation for detection of lumbar disc herniation. The procedure is safe and cost effective. Key words: Lumbar Disc Herniation; Magnatic Resonance Imaging (MRI). DOI: 10.3329/jdmc.v18i1.6298 J Dhaka Med Coll. 2009; 18(1) : 8-14